ANALISIS KEBERHASILAN PENERAPAN SISTEM RFID TERINTEGRASI (STUDI TENTANG END-USER'S KARTU E-TOLL DI TOL JORR 2) - T. Husain (LPPM UNIVERSITAS BINA INSAN, 2020)
Radio Frequency Identification (RFID) is a radio frequency based on identification technology which is a revolution of tracking identification of goods or product tracking in the form of chips with wireless antennas on an object. This research aims to reconfirm the Technology Acceptance Model (TAM) through perceived usefulness and perceived ease-of-use as well as system quality in the DeLone and McLean Models on E-Toll end-user's satisfaction in electronic transaction services. The research type using a quantitative approach with questionnaires as a means of data collection. The number of samples counted by 11 respondents. The data analysis methods using moderated regression by Stata/MP 14.0 through, a test of the quality instrument, classical assumption test, and hypothesis test. The findings represent that the Technology Acceptance Model (TAM) and the IS Success Model prove significant influence as a pure moderator with an increase in the Adjusted R-Square score of 30.07 percent. The Attitude variables only prove the effect of Perceived Ease-of-Use on Satisfaction. The research implication of the Technology Acceptance Model (TAM) and the IS Success Model testing can provide recommendations for academics, especially regarding the end-users of the Integrated RFID System.